P40 Losing the battle? Time to focus the risk discussion with HIV-positive MSM. (23rd May 2012) - Perera, S; McCormack, S; Nwokolo, N
Abstract : Background: BHIVA 2008 Guidelines advocate development of prevention messages promoting sexual health of HIV-positive individuals to minimise onward transmission and acquisition of infections prevalent in such individuals, for example HCV and LGV. Objectives: To assess the extent of unprotected anal intercourse (UAI) in an HIV-positive population attending a London sexual health clinic. To assess transmission and acquisition risks. To describe the nature of sexual health discussions with health care providers. Methods: 50 randomly selected notes of HIV-positive patients were reviewed. Data were collected on demographics, ART, viral load (VL), sexual partners and topics discussed. Results: 66% were from the UK and 74% were >30. 47 (94%) were MSM/Bisexual; 2 (4%) heterosexual females; for 1 (2%) male IVDU, orientation, partners and discussion were not documented. In 8/47 MSM it was unclear if AI had occurred; 1/47 reported AI but condom use was not documented. In 38 sufficiently complete records, all reported AI: 7 (18%) protected AI only, 12 (32%) UAI with positive partners only; 19 (50%) reported UAI with positive and negative partners, although 9/19 (47%) had VL <500. 7/10 MSM reporting UAI who had VL >500 used recreational drugs although only one reported doing so during sex. Discussion was not documented in 17 (34%) notes, and in 12 focus was only on transmission. 19 topics were discussed with no consistency but could be classified as transmission or acquisition related. Transmission risks were discussed in 15 (79%) of the 19 reporting UAI with negative partners; acquisition risks were discussed in 17 (55%) of 31 at risk. Conclusions: Although UAI was reported by the majority of MSM, only 10 reported a clinically relevant risk of transmitting HIV, but the majority were at risk of acquiring HCV/LGV. The diversity in topics noted as discussed suggests that simpler, more focused messages of risk reduction would be helpful to sexual health service users and providers.